2020
DOI: 10.3390/ijerph17165997
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Active Transportation among Children and Adolescents in the Global Matrix 3.0 Initiative: A 49-Country Comparison

Abstract: This article aims to compare the prevalence of active transportation among children and adolescents from 49 countries at different levels of development. The data was extracted from the Report Cards on Physical Activity for Children and Youth from the 49 countries that participated in the Global Matrix 3.0 initiative. Descriptive statistics and a latent profile analysis with active transportation, Human Development Index and Gini index as latent variables were conducted. The global average grade was a “C”, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 93 publications
2
30
0
Order By: Relevance
“…The importance of the economic question can also be extrapolated to the national dimension. The investigation by González, et al [ 52 ] demonstrated that when comparing the prevalence of AC among children and adolescents from 49 countries at different levels of development, countries with a very high Human Development Index have low prevalence of AC and low inequalities, but there are countries, such as the Netherlands, that manage to invert this relation [ 53 ]. Thus, people are more likely to travel by private car and motorcycle by reason of convenience, timeliness, and reliability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the economic question can also be extrapolated to the national dimension. The investigation by González, et al [ 52 ] demonstrated that when comparing the prevalence of AC among children and adolescents from 49 countries at different levels of development, countries with a very high Human Development Index have low prevalence of AC and low inequalities, but there are countries, such as the Netherlands, that manage to invert this relation [ 53 ]. Thus, people are more likely to travel by private car and motorcycle by reason of convenience, timeliness, and reliability [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Active school transportation (AST), also known as cycling and walking to school, is an opportunity to increase PA at the population level [ 4 , 5 ]. Unfortunately, only about 54–59% of children and the youth in Sweden use active transport modes [ 6 ]. This is low compared to neighboring countries such as Finland and Denmark, where 74–79% of children and the youth use active transport.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Global Matrix 3.0, Germany was graded with C– based on reports that ca. 40% of children and adolescents use active modes to commute to school [ 13 ].…”
Section: Introductionmentioning
confidence: 99%